The Requirements for Replacement of Elected Legislative Candidates for Election Based on Democratic Principles - Muhammad Iqbal Maulana Haedar (Jurnal Hukum Volkgeist, 2021)
The research method used is Normative Juridical with a form of data collection by observation and documentation. This research aims to be able to know and analyze how the application of democratic principles and legal implications in the implementation of replacement of elected legislative candidates. The results of the study showed that there are differences in interpretation of the authority in terms of replacement of prospective legislative members elected. Political parties consider themselves to have absolute authority, while based on its rules the KPU should have that authority. Regarding the legal implications of the candidates of elected legislators who are dismissed by his party of course make the elected candidates in question are not appointed as members of the legislature and also give rise to biased legal certainty. Whereas in the legal process has been found the results of a final and binding ruling from the Makassar State Administrative Court.